2016
DOI: 10.4314/ovj.v6i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Post-surgical treatment of thyroid carcinoma in dogs with retinoic acid 9 cis improves patient outcome

Abstract: The objective of the present study was to compare the effects of isotretinoin 9-cis (RA9-cis) as a post-surgery treatment of thyroid carcinoma to a traditional treatment (doxorubicin) and no treatment. Owners who did not want their dogs to receive treatment were placed into the control group A (GA; n=10). The remaining dogs were randomly placed into either group B (GB; n=12) and received doxorubicin at a dose of 30 mg/m 2 every three weeks, for six complete cycles or group C (GC; n=15) and treated with RA9-cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 36 publications
2
15
0
Order By: Relevance
“…However, endothelial cells of compact carcinomas showed higher expression of RARα than those of the other groups (healthy and follicular-compact carcinomas), and further studies are needed to help our understanding of the role of this receptor in carcinoma progression. Retinoic receptor expression in thyroid carcinoma is consistent with our recent study (Castillo et al, 2016) in which isotretinoin 9-cis (RA9-cis) treatment increased time of recurrence and survival time in dogs with follicular-compact and compact thyroid carcinoma when compared to doxorubicin after surgery. Miyajima et al (2006) showed that in canine masts cells, RARα expression was positively correlated with response to retinoic acid treatment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, endothelial cells of compact carcinomas showed higher expression of RARα than those of the other groups (healthy and follicular-compact carcinomas), and further studies are needed to help our understanding of the role of this receptor in carcinoma progression. Retinoic receptor expression in thyroid carcinoma is consistent with our recent study (Castillo et al, 2016) in which isotretinoin 9-cis (RA9-cis) treatment increased time of recurrence and survival time in dogs with follicular-compact and compact thyroid carcinoma when compared to doxorubicin after surgery. Miyajima et al (2006) showed that in canine masts cells, RARα expression was positively correlated with response to retinoic acid treatment.…”
Section: Discussionsupporting
confidence: 90%
“…These factors were expressed at an intermediate level in follicular-compact carcinomas, which is consistent with the degree of differentiation of this type of tumour compared with compact carcinoma. Indeed, we have recently shown (Castillo et al, 2016) that thyroid follicular compact carcinomas had a greater time to recurrence than compact carcinomas in dogs. In the present study, we showed that the pattern of expression of VEGF was similar to that of IGF-1/IGF-1R in the different groups, as demonstrated by the upregulation of VEGF expression in fibroblasts and endothelial cells of compact carcinoma.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[22][23][24][58][59][60][61] There is also a small study reporting the administration of 9-cisretinoic acid, a first generation retinoid, for the treatment of canine thyroid tumour. 62 Overall, no studies have demonstrated improved measures of outcome. As the natural disease is acknowledged to be slowly progressive, SD is difficult to evaluate as representing CB.…”
Section: Discussionmentioning
confidence: 99%
“…Measurable tumour responses between 10 and 54% were reported, but significant improvements in PFIs and OSTs were not demonstrated 22–24,58–61 . There is also a small study reporting the administration of 9‐ cis ‐retinoic acid, a first generation retinoid, for the treatment of canine thyroid tumour 62 . Overall, no studies have demonstrated improved measures of outcome.…”
Section: Discussionmentioning
confidence: 99%